HDAC inhibition induces expression of scaffolding proteins critical for tumor progression in pediatric glioma: focus on EBP50 and IRSp53. Issue 4 (10th November 2019) - Capdevielle, Caroline; Desplat, Angélique; Charpentier, Justine; Sagliocco, Francis; Thiebaud, Pierre; Thézé, Nadine; Fédou, Sandrine; Hooks, Katarzyna B; Silvestri, Romano; Guyonnet-Duperat, Veronique; Petrel, Melina; Raymond, Anne-Aurélie; et al.
Abstract: Background: Diffuse midline glioma (DMG) is a pediatric malignancy with poor prognosis. Most children die less than one year after diagnosis. Recently, mutations in histone H3 have been identified and are believed to be oncogenic drivers. Targeting this epigenetic abnormality using histone deacetylase (HDAC) inhibitors such as panobinostat (PS) is therefore a novel therapeutic option currently evaluated in clinical trials. Methods: BH3 profiling revealed engagement in an irreversible apoptotic process of glioma cells exposed to PS confirmed by annexin-V/propidium iodide staining. Using proteomic analysis of 3 DMG cell lines, we identified 2 proteins deregulated after PS treatment. We investigated biological effects of their downregulation by silencing RNA but also combinatory effects with PS treatment in vitro and in vivo using a chick embryo DMG model. Electron microscopy was used to validate protein localization. Results: Scaffolding proteins EBP50 and IRSp53 were upregulated by PS treatment. Reduction of these proteins in DMG cell lines leads to blockade of proliferation and migration, invasion, and an increase of apoptosis. EBP50 was found to be expressed in cytoplasm and nucleus in DMG cells, confirming known oncogenic locations of the protein. Treatment of glioma cells with PS together with genetic or chemical inhibition of EBP50 leads to more effective reduction of cell growth in vitro and in vivo. Conclusion: Our data reveal a specific relation between HDAC inhibitors and scaffolding protein deregulation which might have a potential for therapeutic intervention for cancer treatment.